Pretreatment Ethanol From Cellulosic - Endah Retno Dyartanti; Margono Margono; Ike Puji Lestari; Muhamad Iqbal Putra; Ulfa Intan Pratiwi (Program studi Teknik Kimia UNS, 2019)
Abstract. Pre-treatment is an important tool for practical cellulose conversion processes and can be carried out in different ways such as mechanical pre-treatment, steam explosion, ammonia fiber explosion, supercritical CO2 treatment, alkali or acid pretreatment, ozone pre-treatment, physicochemical pretreatment, dilute-acid pretreatment and biological pre-treatment. Biomass pretreatment with hot water (HW) is the most investigated physicochemical method use the differences in the thermal stabilities of the major components of lignocellulosic materials. Acid pretreatment of lignocellulosic biomass aims at increasing the sugar substrate digestibility, defined as the concentration of reducing sugars after the hydrolysis, by microorganisms. Acid hydrolysis is an attractive pretreatment method as the hemicellulose degradation runs with the efficiency of approximately 20-90%, depending on the process conditions. Dilute acid (DA) processes with continued research and development, no significant breakthroughs have been made to raise the glucose yields much higher than 65-70%. Acid pretreatment is much more effective than water and alkaline pretreatment in terms of cellulose accessibility increase compared with DA and HW pretreatment. Keywords: ethanol, cellulosic, pre-treatment